2021
DOI: 10.33448/rsd-v10i11.19815
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis of a single prosthesis on a poorly positioned implant

Abstract: The mechanical positioning behavior of a mal-positioned implant was evaluated in the finite element method. Models were created in SolidWorks Professional 2013® software with a single implant rehabilitation. The following were analyzed: Control Group, crown aligned to the implant long axis; Experimental Group, crown shifted 3 mm mesial proximally to the implant axis. Compressive stresses in cortical and medullary bone, and Von Mises stresses in implants and components were evaluated. With 100 N occlusal loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Situations such as pneumatization of the maxillary sinus and bone atrophies are obstacles to the ideal implant placement that may sometimes require regenerative therapies, such as bone grafts. Therefore, depending on the bone availability and the patient-specific anatomy, the implant may be placed in a no-ideal position [14][15][16][17] and consequently will receive oblique loads.…”
Section: Implant Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Situations such as pneumatization of the maxillary sinus and bone atrophies are obstacles to the ideal implant placement that may sometimes require regenerative therapies, such as bone grafts. Therefore, depending on the bone availability and the patient-specific anatomy, the implant may be placed in a no-ideal position [14][15][16][17] and consequently will receive oblique loads.…”
Section: Implant Positioningmentioning
confidence: 99%
“…In summary, patient's rehabilitation with inclined implants will require more frequent monitoring and control of forces, as a previous finite element analysis (FEA) demonstrated that improperly positioned implants result in the highest stresses for all prosthetic components [17]. Additionally, failure at the screw-joint interface can also be associated with the presence of inclined implants.…”
Section: Implant Positioningmentioning
confidence: 99%